Magnetic resonance-guided laser interstitial thermal therapy vs. stereoelectroencephalography-guided radiofrequency thermocoagulation in epilepsy patients with focal cortical dysplasia: a systematic review and meta-analysis - Li, Yiming; Gao, Jiayi; Ye, Zi; Mu, Jie (Frontiers in Neurology, 2023)
Background Magnetic resonance-guided laser interstitial thermal therapy (MRgLiTT) and stereoelectroencephalography-guided radiofrequency thermocoagulation (SEEG-RFTC) are two effective, minimally invasive treatments for epilepsy with focal cortical dysplasia (FCD). The purpose of this study is to conduct a meta-analysis to evaluate and compare the efficacy and safety of these two therapies in epilepsy patients with FCD. Methods We searched PubMed, Embase, Cochrane, and other databases for articles published before March 2023. The primary objective was to compare the effectiveness and complications of MRgLiTT and SEEG-RFTC in epilepsy patients with FCD. The second objective was to determine which method provides a better prognosis for specific subgroup patients. Results According to the inclusion and exclusion criteria, 18 studies were included, comprising 270 FCD patients including 37 patients from 6 MRgLiTT studies and 233 from 12 SEEG-RFTC studies. There were no significant differences between MRgLiTT and SEEG-RFTC groups in the seizure-freedom rate (59%, 95% CI 44–74%; 52%, 95% CI 47–57%, P = 0.86) and the rate of ≥50% seizure-reduction of FCD (90%, 95% CI 80–100%; 90%, 95% CI 86–94%, P = 0.42). Both methods had low complication rates (17.1%, 28/159) and long-term complication (2.5%, 4/159) rate, with no significant difference between them (P = 0.17). Conclusion Both MRgLiTT and SEEG-RFTC are safe and minimally invasive treatments for patients with FCD. They have comparable performance in terms of postoperative seizure-freedom rates in patients with FCD, and both can be used as treatment options for patients with FCD. Our study found that SEEG-RFTC had a better therapeutic effect in the FCD2b subgroup.